Changes in microbial utilization and fate of soil carbon following the addition of different fractions of anaerobic digestate to soils. (15th February 2021) - Cattin, Marta; Semple, Kirk T.; Stutter, Marc; Romano, Gaetano; Lag‐Brotons, Alfonso J.; Parry, Chris; Surridge, Ben W. J.
Abstract: Applying digestate, the residue from anaerobic digestion, to soil as a replacement for inorganic fertiliser is of growing interest in agriculture. However, the impacts of different fractions of digestate on the soil carbon (C) cycle remain unclear and provide the focus for the research reported here. We examined the effects of applying whole digestate (WD) and solid digestate (SD) on carbon dioxide (CO2 C) efflux, the concentrations of dissolved organic carbon (DOC), microbial biomass C (Cmicro ) and phospholipid fatty acids, alongside carbon use efficiency (CUE). A 21‐day laboratory microcosm incubation was used to investigate the impacts of digestate when applied to two grassland soils of high versus low initial nutrient content. Application rates for SD and WD were based on recommended nitrogen (N) inputs to grassland soils for these organic materials. Compared to control treatments, cumulative CO2 C efflux and the concentration of DOC increased significantly after WD and SD application, although only within the low nutrient soil. Both Cmicro and the fungal‐to‐bacterial ratio increased significantly following SD application, regardless of the initial soil nutrient content. These observations are likely to reflect the larger input of C, alongside the dominance of more strongly lignified compounds, associated with SD compared to WD to achieve a constant N application rate. Our results also indicate that the two digestate fractions generated significantly different CUE. The application of SD led to increases in Cmicro and positive values of CUE, whereas decreases in Cmicro and negative values of CUE were observed following WD application. These findings emphasize the need to carefully plan the management of digestate in agricultural production systems, to minimize negative impacts on C storage within soils whilst maximizing the agronomic value derived from digestate. Highlights: Past research has not fully elucidated the impacts of digestate fractions on the soil C cycle. Soil nutrient status + digestate fraction shown to impact microbial community and CO2 C efflux. Solid digestate fraction has positive impacts on microbial biomass and carbon use efficiency.